225 Sporadic inclusion body myositis: a longitudinal observational study investigating outcome measures for clinical trials. Issue 12 (14th November 2019) - Sangha, Gina; Skorupinska, Iwona; Germain, L; Bellin, A; Parton, Matthew; Hanna, Michael; Miller, James; Hilton-Jones, David; Freebody, Jane; Machado, Pedro
Abstract : Background: Sporadic inclusion body myositis (IBM) is the most common age-related acquired myopathy. Our aim was to longitudinally evaluate clinical, quantitative and functional characteristics of the disease to develop statistical models of progression that can be used in clinical trials. Methods: In a prospective cohort study, we recruited 205 patients with a diagnosis of IBM across three centres (London, Oxford and Newcastle). Patients underwent bilateral manual muscle testing (MRC scale), quantitative muscle testing and disability scoring (IBM Functional Rating Scale) at each follow up visit. The time at which a patient first required a mobility aid was recorded. Linear multilevel models were fitted to investigate the progression of these scores over time. Cox proportional hazards regression was used to model time to use of a mobility aid. Results: In the preliminary analyses we have generated reliable multilevel models of disease progression using those muscle groups that are worst affected by the disease over time. We have also modelled the progression of IBMFRS over time. These models can be used to predict/monitor disease progression. Conclusion: This study will be the largest prospective observational study in IBM to date and will reveal useful outcome measures that can be used in clinical trials.